PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN IPA MATERI GAYA DAN GERAK UNTUK KELAS IV SD - Wina Widyawati, - (2021)
Android-based learning media is one of the innovations in the development of digital learning media. In this study, researchers developed an android-based learning media for science subjects using the Design and Development (DnD) research method and using the ADDIE development model consisting of several stages, namely analysis, design, development, implementation, and evaluation. Participants involved in this study are one media expert, one material expert, one teacher as a learning practitioner, and 15 students grade IV at SDN 150 Gatot Subroto. The results showed that the assessment of the media expert got a score with a percentage of 86%, the material expert got a score with a percentage of 98%, and from the teacher as a learning practitioner got a score with a percentage of 91%. All assessments obtained from participants fall into the "Very Eligible" category. The level of effectiveness of learning media on learning outcomes has a significant increase in value, in the pre-test results, the completeness of learning is only 7% but in the post-test results, after students use learning media, the students' learning completeness also increases significantly at a percentage of 73% .